Dampak Ekosistem Digital terhadap Kesejahteraan Kolektif Pembudidaya Ikan Gurame dan Masyarakat Sekitar di Dusun Turalak Kabupaten Ciamis - Ganjar Santika; Agus Sahroni; Arif Syaripudin; Asep Asep; Lepiyani Lepiyani (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study aims to analyse the impact of socio-economic engineering through the use of digital ecosystems (TikTok) on the welfare of the local community and gurame fish farmers in Turalak. Amidst the dominance of traditional systems, the use of social commerce (TikTok) has emerged as an instrument of change that is transforming the behaviour and structure of rural communities. The method employed is qualitative with a descriptive approach. Data was collected through observation, interviews with fish farmers, local workers, and relevant social media administrators. The research findings indicate that digitalisation can stimulate the process of disintermediation, which can grant price autonomy to fish farmers and expand market reach. This phenomenon creates social engineering in the form of new economic roles, such as social media administrators, packaging staff, and local couriers. From a Sharia perspective, this can foster collective welfare through fairer and more transparent income distribution. It can be concluded that the digital ecosystem can act as a catalyst for social structural change, collectively improving the standard of living of the surrounding community